Makna dan Pengalaman Motivasi Belajar Siswa SMA di Era Digital: Studi Fenomenologis di Kota Depok - Mhd. Fadhil Kurniawan; Rilla Sovitriana (CV. ITTC INDONESIA, 2026)
The development of digital technology has changed the way students learn and access information. While digital technology offers various conveniences in the learning process, its presence also poses challenges in the form of social media distractions, decreased learning focus, and changes in students' learning motivation patterns. Therefore, a deeper understanding of how students interpret and experience learning motivation in the digital era is needed. This study aims to understand the meaning and experiences of high school students' learning motivation in the digital era. This study used a qualitative approach with a phenomenological method. Data were collected through in-depth interviews with eight high school students in Depok City who actively use digital technology in their learning activities. Data analysis was conducted using thematic analysis techniques based on Braun and Clarke's guidelines.The results show that students interpret learning motivation as an internal drive to achieve academic goals, which is strengthened by access to digital technology. Intrinsic motivation arises from interest in the material, curiosity, and personal satisfaction, while extrinsic motivation is influenced by parental demands, the school environment, and expectations of achievement. The digital era provides learning convenience, but also presents challenges in the form of social media distractions and decreased learning focus. In general, students who are able to manage the use of technology in a balanced manner show a more stable and positive level of learning motivation. This finding emphasizes the important role of self-awareness and self-regulation in maintaining learning motivation in the digital era. Keywords: learning motivation, digital era, phenomenology, intrinsic motivation, extrinsic motivation.